EVALUASI PENYAJIAN LAPORAN KEUANGAN BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA CV. SHAFIRA MARGA UTAMA - Balqis, Aura Queensy; Tyas, Alvy Mulyaning (Politeknik Negeri Ambon, 2025)
Introduction: This research aims to assess how financial statements are presented at CV. Shafira Marga Utama has been carried out in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP), CV. Shafira Marga Utama falls into the category of businesses required to apply SAK ETAP in preparing their financial statements.Method: This research employs a qualitative descriptive method, using interviews and document analysis for data collection. This approach is chosen to gain a deeper understanding of the company's financial statement preparation practices.Results: The research findings indicate that the company has prepared financial statements in including a balance sheet and an income statement. However, the presentation of these reports does not fully comply with the provisions of SAK ETAP, as it does not include a statement of cash flows, an equity movement report and explanatory notes on the financial reports. Therefore, it is recommended that the company enhance its understanding of applicable accounting standards to produce more complete, informative, and reliable financial statements. Keywords: Financial Statements, SAK ETAP